2016
DOI: 10.1158/1078-0432.ccr-16-0153
|View full text |Cite
|
Sign up to set email alerts
|

DDGP versus SMILE in Newly Diagnosed Advanced Natural Killer/T-Cell Lymphoma: A Randomized Controlled, Multicenter, Open-label Study in China

Abstract: DDGP chemotherapy resulted in significant improvement in PFS, OS, and better tolerability compared with SMILE chemotherapy for newly diagnosed advanced NK/T-cell lymphoma patients. Clin Cancer Res; 22(21); 5223-8. ©2016 AACR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 28 publications
2
97
2
1
Order By: Relevance
“…This survival benefit may be due to introducing rituximab. To date, gemcitabine-based combination chemotherapy has been demonstrated to be highly successful in improving the treatment outcome of T/NK-cell lymphoma (33)(34)(35). However, in the present study patients with T/NK-cell LAHS who were treated with gemcitabine did not exhibit survival advantage.…”
Section: T/nk-cell Lymphomacontrasting
confidence: 69%
See 1 more Smart Citation
“…This survival benefit may be due to introducing rituximab. To date, gemcitabine-based combination chemotherapy has been demonstrated to be highly successful in improving the treatment outcome of T/NK-cell lymphoma (33)(34)(35). However, in the present study patients with T/NK-cell LAHS who were treated with gemcitabine did not exhibit survival advantage.…”
Section: T/nk-cell Lymphomacontrasting
confidence: 69%
“…L-asp/peg-based regimens were analyzed in the ENKL group and led to an improved prognosis. L-asp/peg-containing regimens have been indicated to be highly effective for patients with NK/T-cell lymphoma (35). The prior studies also demonstrated that the significant efficacy and safety profile of the peg-based regimen in the treatment of newly diagnosed and relapsed/refractory ENKL (35)(36)(37).…”
Section: T/nk-cell Lymphomamentioning
confidence: 99%
“…24 Recently, some studies have demonstrated the efficacy of l-ASP/peg-asparaginase-based chemotherapy in ENKTCL ( l-ASP/peg-asparaginase-based regimens have also demonstrated good efficacy in newly diagnosed advanced-stage NK/T-cell lymphoma, with a CR rate of 29%-71% and a 1-year OS rate of 45%-90%. 24,32,34 The P-GEMOX regimen was proven to be effective and well tolerated in newly diagnosed stage III/IV and relapsed/refractory ENKTCL in a retrospective study that included 35 patients. 13 In that study, the 3-year OS and PFS rates were 64.7% and 38.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another L-asparaginase-containing regimen DDGP (dexamethasone, gemcitabine, cisplatinum, and pegaspargase) was compared with SMILE in a phase III randomized trial for untreated advanced-stage NK/T-cell lymphoma [74]. Twenty-one patients received DDGP, achieving ORR and CR rate of 95 and 71%.…”
Section: Introductionmentioning
confidence: 99%